Tlcp fiber composite material, method of making and use in satellite solar wings
Patent Information
- Application Number
- CN202611301781.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]为了解决TLCP纤维复合材料界面性能不足、织物面外性能损失明显且难以工业化连续处理的问题,本申请提供了一种TLCP纤维复合材料及其制备方法和应用
(1)通过织物态固态缩聚处理,实现TLCP纤维分子链增长与织物经纬交叉点热融合,纤维本体强度模量得到了提升,并构建了区别于纤维-基体界面的第二载荷传递通道,相比未进行固态缩聚处理的方案,层间剪切强度和界面剪切强度分别提升约18%和21%。
Smart Images

Figure REF-OBJ-1787726061539-000001 
Figure REF-OBJ-1787726061539-000002
Abstract
Description
Technical Field
[0001] This application relates to the field of composite materials technology, specifically to TLCP fiber composite materials, their preparation methods, and their application in satellite solar panels. Background Technology
[0002] With the development of aerospace technology, structural components such as flexible solar panel substrates for satellites are facing increasingly stringent requirements for lightweight, low dielectric loss, and high dimensional stability in their structural materials. Thermotropic liquid crystal polymer (TLCP) fibers, with their low dielectric constant, low dielectric loss, low density, low moisture absorption, and good radiation resistance, are ideal reinforcements for preparing low dielectric loss aerospace structural composite materials. Cyanate ester resin (CE) also possesses low dielectric constant, low dielectric loss, and good resistance to damp heat. The composite system of these two materials shows broad application prospects in high-frequency signal transmission structural components such as flexible solar panel substrates for satellites.
[0003] TLCP fibers have a chemically inert surface and low surface energy, resulting in insufficient interfacial adhesion to the cyanate ester resin matrix. This leads to low interlaminar shear strength and interfacial shear strength in the composite material, restricting its engineering applications. Furthermore, commercial TLCP fibers are typically heat-treated as monofilaments or yarns. When woven into fabrics, the load is transferred at the warp and weft intersections solely through friction between the yarns, resulting in a single out-of-plane load transfer channel and significant loss of out-of-plane properties.
[0004] To improve the interfacial bonding between TLCP fibers and the resin matrix, existing technologies typically employ plasma treatment to activate the fiber surface. However, conventional low-pressure plasma treatment requires a vacuum chamber, which is insufficient for the continuous industrial processing requirements of large-format fabrics. Furthermore, existing technologies often use a single layer of silane coupling agent to treat the fiber surface. This treatment only provides chemical anchoring and cannot create an interfacial modulus gradient transition layer between the fiber and the matrix. An abrupt modulus step still exists between the fiber and the matrix, making them prone to interfacial debonding under load. Therefore, how to maintain the low dielectric loss advantage of TLCP fiber composites while improving their interlaminar shear strength and interfacial shear strength, and achieving continuous industrial processing of large-format fabrics, is a problem that needs to be solved in this field. Summary of the Invention
[0005] To address the issues of insufficient interfacial properties, significant loss of out-of-plane properties of TLCP fiber composites, and difficulty in industrialized continuous processing, this application provides a TLCP fiber composite material, its preparation method, and its application.
[0006] The first aspect of this application provides a method for preparing a TLCP fiber composite material, comprising the following steps: performing solid-state polycondensation treatment on a TLCP fiber fabric at a temperature below the melting point of the TLCP fiber to obtain a first fabric; performing atmospheric pressure plasma activation treatment on the first fabric to obtain a second fabric; sequentially coating the fiber surface of the second fabric with an epoxy-based silane coupling agent base layer and a functional coating to form a double-layer silane coupling agent interface layer, wherein the functional coating comprises an epoxy-based silane coupling agent and an amino-based silane coupling agent to obtain a third fabric; impregnating the third fabric with cyanate ester resin, and curing it through layup and stepped hot pressing to obtain the TLCP fiber composite material.
[0007] The solid-state polycondensation treatment in this application is carried out at a temperature close to but below the melting point. At this temperature, the molecular chains in the amorphous region of the TLCP fiber continue to grow through polycondensation in the solid state, thereby increasing the strength and modulus of the fiber body. The fibers at the warp and weft intersections of the fabric undergo thermal fusion at high temperatures, forming physical fusion points. These physical fusion points constitute a second load transfer channel distinct from the fiber-matrix interface, improving the out-of-plane properties of the fabric. Atmospheric pressure plasma activation treatment continuously processes the fabric surface under atmospheric pressure, eliminating the need for a vacuum chamber. This is suitable for the industrial continuous production of large-format fabrics and can introduce oxygen-containing polar functional groups onto the fiber surface, increasing the fiber surface free energy and the density of anchorable sites for coupling agents, providing a foundation for subsequent chemical bonding with silane coupling agents. In the bilayer silane coupling agent interface layer, the epoxy-based silane coupling agent base layer forms a chemical anchor with the fiber surface. The amino-based silane coupling agent in the functional coating provides primary / secondary amino groups. These amino groups catalyze the trimerization cyclization reaction of cyanate ester groups, preferentially cyclizing the cyanate ester groups in the interface region. This results in a higher crosslinking density in the interface region compared to the bulk matrix, automatically forming a gradient transition layer of crosslinking density and modulus between the fiber surface and the bulk matrix. This eliminates abrupt modulus jumps and avoids interfacial stress concentration. Stepped hot-pressing curing ensures the stable formation of the interfacial gradient structure and the curing of the resin matrix.
[0008] Furthermore, the solid-state polycondensation treatment temperature is 250-300℃, which is more than 10℃ lower than the melting point of the TLCP fiber; the holding time for the solid-state polycondensation treatment is 2-12 hours, and the heating rate is 2-10℃ / hour; the solid-state polycondensation treatment is carried out under vacuum or an inert atmosphere. Specifically, the solid-state polycondensation treatment temperature can be selected from any one of 250℃, 260℃, 270℃, 280℃, 290℃, and 300℃, or a range between any two; the holding time can be selected from any one of 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, and 12 hours, or a range between any two. If the temperature is too low or the holding time is too short, the molecular chain growth is insufficient, the degree of cross-point fusion is low, it is difficult to form an effective second load transfer channel, and the improvement of out-of-plane properties is limited; if the temperature is too high, it will cause the fiber to melt and spin, and the fabric structure to collapse; if the heating rate is too fast, it will easily cause internal temperature gradient and thermal stress damage to the fiber, while if it is too slow, it will prolong the production cycle and reduce efficiency.
[0009] Furthermore, the solid-state polycondensation treatment is carried out at a temperature of 280-300℃, with a holding time of 4-8 hours and a heating rate of 3-6℃ / hour. Within this range, the fiber molecular chains grow sufficiently and the warp and weft intersections fuse to a high degree, maintaining the integrity of the fabric structure while ensuring processing efficiency.
[0010] Furthermore, the atmospheric pressure plasma activation treatment employs an atmospheric pressure plasma jet with a discharge power of 100-500W, a fabric speed of 1-10m / min, a nozzle-to-fabric distance of 3-15mm, and a treatment atmosphere of compressed air or an O2 / N2 mixture. Specifically, the discharge power can be selected from any one or a range between 100W, 150W, 200W, 250W, 300W, 350W, 400W, 450W, and 500W; the fabric speed can be selected from any one or a range between 1m / min, 2m / min, 3m / min, 5m / min, 8m / min, and 10m / min. If the discharge power is too low, the fabric speed too fast, or the nozzle distance too large, the treatment dosage will be insufficient, resulting in a small introduction of surface functional groups and limited improvement in the coupling agent anchoring density. Conversely, if the discharge power is too high or the nozzle distance too small, it may damage the fiber surface structure, thereby reducing the fiber's bulk strength. After plasma activation, the surface free energy of the fiber can be increased to over 45 mN / m, providing a sufficient anchoring foundation for the subsequent chemical bonding of the bilayer silane coupling agent interface layer.
[0011] Further, the epoxy silane coupling agent is γ-glycidoxypropyltrimethoxysilane, and the amino silane coupling agent is γ-aminopropyltriethoxysilane; both the base coating and the functional coating are dried after application, with a drying temperature of 60-80℃ and a drying time of 10-40 min. Specifically, the silanol generated by the hydrolysis of the epoxy silane coupling agent undergoes a condensation reaction with the hydroxyl groups on the fiber surface introduced by plasma activation, forming a chemically anchored base coating. Its epoxy groups can also participate in the curing reaction of the cyanate ester resin, realizing a chemical bridge between the fiber and the resin; the amino silane coupling agent in the functional coating provides primary / secondary amino groups, providing catalytic sites for the preferential trimerization of cyanate ester groups in the interface region.
[0012] Further, the cyanate resin is a bisphenol A type, bisphenol B type, bisphenol F type, phenolic type or naphthalene type cyanate resin, or a resin formed by blending cyanate resin and bismaleimide resin in a weight ratio of 90:10 to 70:30; the cyanate resin also includes a catalyst, the catalyst being selected from at least one of stannous octoate, copper naphthenate and cobalt acetylacetonate, and the amount of catalyst added is 50-500 ppm. Specifically, the aforementioned cyanate ester resins all possess low dielectric constant, low dielectric loss, and good resistance to damp heat. Among them, bisphenol A and bisphenol F cyanate ester resins have mature processes and moderate costs, while phenolic and naphthalene-type cyanate ester resins have higher crosslinking density and heat resistance. The introduction of bismaleimide resin can copolymerize with cyanate ester groups to form an interpenetrating network, thereby improving the toughness of the matrix. The catalyst can reduce the activation energy of the trimerization reaction of cyanate ester groups, promoting the curing reaction. The addition amount in the range of 50-500 ppm can ensure the normal progress of the curing reaction while reserving sufficient reaction window for the formation of the interfacial gradient structure.
[0013] Further, the TLCP fiber is a thermotropic liquid crystal polymer fiber copolymerized with p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, wherein the molar ratio of p-hydroxybenzoic acid to 6-hydroxy-2-naphthoic acid is (70-75):(25-30); the monofilament diameter of the TLCP fiber is 8-20 μm, and the multifilament linear density is 100-2000 dtex; the TLCP fiber fabric is a plain weave or satin weave fabric with an areal density of 50-200 g / m². 2 Specifically, the main chain of HBA / HNA copolymer TLCP fiber is composed of rigid aromatic ester segments, which endows the fiber with low dielectric constant, low dielectric loss, low density and electrical insulation properties; plain weave fabric has stable structure and good rigidity, while satin weave fabric has good drape and curved surface fit, and can be selected according to the rigidity of the substrate and the laying requirements.
[0014] Further, the stepped hot-press curing includes: holding at 120-140℃ for 1-2 hours, then holding at 180-200℃ for 2-3 hours, and then holding at 220-240℃ for 2-3 hours, with a curing pressure of 0.4-0.7 MPa. Specifically, the stepped hot-press curing completes curing by sequentially holding at multiple temperature stages and gradually increasing the temperature, ensuring the stable formation of the interface gradient structure and the full curing of the resin matrix.
[0015] A second aspect of this application provides a TLCP fiber composite material obtained by the aforementioned preparation method. In this composite material, TLCP fibers are distributed in a woven form within a cyanate ester resin matrix, and the fiber surface has a double-layer silane coupling agent interface layer, with a gradient transition distribution of crosslinking density and modulus in the interface region. This composite material possesses both low dielectric constant and low dielectric loss, along with good interlaminar shear strength and interfacial shear strength. Its dielectric constant is ≤3.0, dielectric loss is ≤0.005 (10GHz), interlaminar shear strength is ≥45MPa, and interfacial shear strength is ≥40MPa, eliminating the need for an additional insulating layer.
[0016] A third aspect of this application provides the application of the aforementioned TLCP fiber composite material in a flexible satellite solar panel substrate. The flexible satellite solar panel substrate has a layup of [0 / 90]3s, [0 / 90]4s, or [0 / 45 / 90 / -45]2s, and the substrate thickness is 0.1-2.0 mm. Because TLCP fibers themselves are electrically insulating and have low dielectric loss, the composite material does not require an additional insulating layer, which reduces the substrate weight and simplifies the manufacturing process.
[0017] This application has the following beneficial effects: (1) By solid-state polycondensation treatment of fabric, the growth of TLCP fiber molecular chains and thermal fusion of the warp and weft intersection of the fabric are realized, the strength modulus of the fiber body is improved, and a second load transfer channel different from the fiber-matrix interface is constructed. Compared with the scheme without solid-state polycondensation treatment, the interlaminar shear strength and interfacial shear strength are increased by about 18% and 21%, respectively.
[0018] (2) Through continuous activation by atmospheric pressure plasma jet, large-format fabrics can be continuously surface treated under atmospheric pressure without the need for a vacuum chamber, making it suitable for industrial mass production; after activation, the surface free energy of the fiber can be increased to more than 45mN / m, and the bonding density of the coupling agent increases.
[0019] (3) By designing the interface of the double-layer silane coupling agent, a transition layer of crosslinking density and modulus gradient is automatically constructed in the fiber interface region to eliminate interface stress concentration. Compared with the treatment of only a single-layer coupling agent, the interface shear strength is increased by about 28%. Compared with no surface treatment, the interlayer shear strength and the interface shear strength are increased by about 73% and about 109%, respectively.
[0020] (4) The resulting composite material has a dielectric constant ≤3.0, a dielectric loss ≤0.005 (10GHz), and a low density (1.31-1.33 g / cm³). 3 TLCP fibers are electrically insulating and do not require additional insulating layers, giving them a clear advantage in lightweighting satellite flexible solar panel substrates and high-frequency signal transmission scenarios. Detailed Implementation
[0021] To facilitate understanding of this application, a more comprehensive description is provided below. This application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to make the disclosure of this application more readily and thoroughly understood.
[0022] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of the application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified. In the description of this application, "several" means at least one, such as one, two, etc., unless otherwise explicitly specified.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0024] In this application, the technical features described in an open-ended manner include both closed technical solutions composed of the listed features and open technical solutions that include the listed features.
[0025] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe features or characteristics, the ranges may be merged. That is, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0026] Unless otherwise specified, the percentage content mentioned in this application refers to mass percentage for solid-liquid mixtures and solid-phase-solid mixtures, and volume percentage for liquid-phase-liquid mixtures.
[0027] Unless otherwise specified, all percentage concentrations mentioned in this application refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of that component.
[0028] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows for temperature fluctuations within the precision range controlled by the instrument.
[0029] To enable those skilled in the art to better understand the present application, the technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are merely some embodiments of the present application, and not all embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present application.
[0030] In this application, TLCP is an abbreviation for Thermotropic Liquid Crystalline Polymer, referring to aromatic copolyester polymers whose molecular chains can form an ordered liquid crystal arrangement in the molten state and can obtain high modulus and high orientation degree through spinning orientation. HBA refers to p-hydroxybenzoic acid, and HNA refers to 6-hydroxy-2-naphthoic acid. These two are the main comonomers in the molecular chain of the TLCP fiber copolymer of this application. The molar ratio of HBA to HNA determines the liquid crystallization, melting point, and mechanical properties of the fiber. Solid-state polycondensation treatment (SSP) refers to a heat treatment process in which the end groups of the amorphous molecular chains of the polymer continue to undergo polycondensation reaction in the solid state within a temperature range below the melting point of the polymer and above the glass transition temperature, thereby achieving molecular chain growth.
[0031] This application utilizes solid-state polycondensation in a woven fabric state, causing thermal fusion of fibers at the warp and weft intersections while the molecular chains grow. Atmospheric pressure plasma jetting refers to a surface treatment method where high-energy active particles (including electrons, ions, excited-state molecules, etc.) generated by discharge under atmospheric pressure are jetted onto the material surface to physically bombard and chemically react with the surface, introducing oxygen-containing polar functional groups. Unlike low-pressure plasma treatment, which requires a vacuum chamber, this method allows for continuous processing of large-format fabrics.
[0032] A bilayer silane coupling agent interface layer refers to a multilayer interface structure consisting of an inner epoxy-based silane coupling agent base layer and an outer functional coating layer containing both epoxy-based and amino-based silane coupling agents. The epoxy-based silane coupling agent is a silane coupling agent containing epoxy functional groups, such as γ-glycidoxypropyltrimethoxysilane (KH-560); the amino-based silane coupling agent is a silane coupling agent containing amino functional groups, such as γ-aminopropyltriethoxysilane (KH-550).
[0033] Stepped hot-press curing refers to a process in which curing is achieved by sequentially holding the material at multiple temperature stages and gradually increasing the temperature under hot-press conditions. In this application, it is divided into three holding stages: 120-140℃, 180-200℃, and 220-240℃. ILSS refers to interlaminar shear strength, reflecting the ability of laminated composite materials to resist shear failure between layers; IFSS refers to interfacial shear strength, reflecting the interfacial bonding strength between the fiber and the matrix. Dk refers to relative permittivity, and Df refers to dielectric loss tangent, characterizing the energy storage and loss characteristics of the material under an alternating electric field. The lower the values of both, the less energy loss the material experiences in high-frequency signal transmission. CE refers to cyanate ester resin, BMI refers to bismaleimide resin; BADCy refers to bisphenol A type cyanate ester resin, and BFDCy refers to bisphenol F type cyanate ester resin.
[0034] In some embodiments of this application, the amount of catalyst added can be selected from any one or a range between any two of 50ppm, 100ppm, 150ppm, 200ppm, 300ppm, 400ppm, and 500ppm, i.e., any value within the range of 50-500ppm; the weight ratio of cyanate ester resin to bismaleimide resin can be selected from any one or a range between any two of 90:10, 85:15, 80:20, 75:25, and 70:30, i.e., 90:10 to 70. The TLCP fiber volume fraction in the composite material can be selected from any one of 35%, 40%, 45%, 48%, 50%, 52%, 55%, 60%, or any value between any two, i.e., any value within the range of 35-60%. The thickness of the flexible solar panel substrate can be selected from any one of 0.1mm, 0.5mm, 1.0mm, 1.5mm, 2.0mm, or any value between any two, i.e., any value within the range of 0.1-2.0mm. The amount of catalyst added is based on the total mass of cyanate ester resin and bismaleimide resin, and the TLCP fiber volume fraction is based on the total volume of the composite material. When the above parameters are taken within the above ranges, they can maintain the low dielectric properties of the composite material while taking into account the interfacial properties and lightweight structure. Moreover, the values of each parameter are independent of each other, and those skilled in the art can combine and select them according to actual needs.
[0035] This application involves solid-state polycondensation treatment of TLCP fiber fabrics in the woven state, specifically, solid-state polycondensation of TLCP fibers in the woven state within a temperature range below the melting point of TLCP fibers and above the glass transition temperature. Solid-state polycondensation in the woven state achieves two effects simultaneously: firstly, the end groups of the molecular chains in the amorphous regions of the fibers continue to undergo polycondensation reactions in the solid state, leading to chain growth, which enhances the strength and modulus of the fiber itself; secondly, the fibers at the warp and weft intersections undergo localized thermal fusion at high temperatures, forming physical fusion points. These physical fusion points constitute a second load transfer channel distinct from the fiber-matrix interface. This second load transfer channel can directly share the load under out-of-plane loads, reducing reliance on the fiber-matrix interface and thus improving the out-of-plane properties of the fabric. In some embodiments of this application, the temperature of the solid-state polycondensation treatment can be selected from any one or a range of any two of 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, and 300°C, and the temperature is more than 10°C lower than the melting point of the TLCP fiber.
[0036] The melting point of TLCP fibers varies with the molar ratio of HBA to HNA. In this application, the temperature window for solid-state polycondensation treatment is set according to the melting point of the selected TLCP fibers. TLCP fibers with different melting points can achieve molecular chain growth and thermal fusion at the warp and weft intersections within a corresponding temperature window that is at least 10°C lower than their melting point. The holding time can be selected from any one of 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h, or any value between any two. The heating rate can be selected from any one of 2°C / h, 3°C / h, 4°C / h, 5°C / h, 6°C / h, 7°C / h, 8°C / h, 9°C / h, and 10°C / h, or any value between any two. Within the above-mentioned ranges, the temperature, holding time, and heating rate of solid-state polycondensation treatment are beneficial to maintaining the integrity of the fabric structure while achieving sufficient molecular chain growth and cross-point thermal fusion. When the temperature is too low or the holding time is too short, the molecular chain growth is insufficient, the degree of cross-point fusion is low, it is difficult to form an effective second load transfer channel, and the improvement of out-of-plane properties is limited. When the temperature is too high (close to or exceeding the melting point), it will cause the fibers to melt and spin, and the fabric structure to collapse. When the heating rate is too fast, it is easy to cause internal temperature gradient and thermal stress damage to the fibers, while when it is too slow, it will prolong the production cycle and reduce efficiency.
[0037] In some embodiments of this application, the atmospheric pressure plasma activation treatment employs an atmospheric pressure plasma jet, which generates a jet containing high-energy active particles (including electrons, ions, excited-state molecules, etc.) through discharge under atmospheric pressure and sprays it onto the fabric surface for continuous treatment. The atmospheric pressure plasma jet can physically bombard and chemically react with the fabric surface, introducing oxygen-containing polar functional groups (mainly hydroxyl groups) onto the fiber surface. This increases the fiber surface free energy and the density of active sites available for condensation anchoring of silane coupling agents, providing a sufficient anchoring foundation for the subsequent chemical bonding of the bilayer silane coupling agent interface layer. Simultaneously, the atmospheric pressure plasma jet operates at atmospheric pressure, eliminating the need for a vacuum chamber, and allows for continuous surface treatment of large-format fabrics, making it suitable for industrial continuous production.
[0038] The discharge power can be selected from any one of 100W, 150W, 200W, 250W, 300W, 350W, 400W, 450W, and 500W, or any value between two of them; that is, any value within the range of 100-500W. The cloth-walking speed can be selected from any one of 1m / min, 2m / min, 3m / min, 4m / min, 5m / min, 6m / min, 7m / min, 8m / min, 9m / min, and 10m / min, or any value between two of them. The discharge power, fabric speed, and nozzle distance can be any value within the range of 1-10 m / min; the distance between the nozzle and the fabric can be selected from any one of 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, and 15 mm, or any value between any two of these, i.e., any value within the range of 3-15 mm; the treatment atmosphere can be compressed air or an O2 / N2 mixture, wherein the volume ratio of O2 to N2 can be 30:70 to 60:40 (based on the total volume of the mixture). Discharge power, fabric speed, and nozzle distance within the above ranges are beneficial for introducing sufficient surface functional groups while avoiding damage to the fiber surface structure: if the discharge power is too low, the fabric speed is too fast, or the nozzle distance is too large, the treatment dosage is insufficient, the amount of surface functional groups introduced is small, and the increase in coupling agent anchoring density is limited; if the discharge power is too high or the nozzle distance is too small, it may damage the fiber surface structure, thus reducing the fiber strength. After plasma activation, the surface free energy of the fiber can be increased to over 45 mN / m. The activation effect of atmospheric pressure plasma treatment on the chemical scale of the fiber surface, combined with the fusion effect of solid-state condensation in the fabric on the structural scale, provides a surface chemical basis for the construction of the bilayer silane coupling agent interface layer.
[0039] After plasma activation, oxygen-containing polar functional groups are introduced into the fiber surface. However, if the coupling agent is applied in a single layer, it can only provide chemical anchoring. There is still a sudden modulus step between the fiber and the matrix. Under load, stress concentration is easily generated in the interface region, resulting in debonding. In view of this, this application sequentially constructs an epoxy-based silane coupling agent base layer and a functional coating on the activated fiber surface to form a double-layer silane coupling agent interface layer: the silanol generated by the hydrolysis of the epoxy-based silane coupling agent undergoes a condensation reaction with the hydroxyl groups on the fiber surface to form a chemically anchored base layer. Its epoxy groups can also participate in the curing reaction of the cyanate ester resin to achieve chemical bridging between the fiber and the resin. The amino-based silane coupling agent in the functional coating provides primary / secondary amino groups. The amino groups have a catalytic effect on the trimerization reaction of the cyanate ester groups, so that the cyanate ester groups in the interface region preferentially cyclize. The crosslinking density in the interface region is higher than that in the bulk matrix, thereby automatically forming a crosslinking density and modulus gradient transition layer between the fiber surface and the bulk matrix, eliminating the abrupt modulus step between the fiber and the matrix, avoiding interface stress concentration, and thus improving the interlayer shear strength and interface shear strength.
[0040] In some embodiments of this application, the concentration of the primer coating solution can be selected from any one of 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, or any value between any two, i.e., any value within the range of 0.5-3wt%; the concentration of the functional coating solution can be selected from any one of 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, or any value between any two, i.e., any value within the range of 0.5-3wt%; the molar ratio of epoxy silane coupling agent to amino silane coupling agent in the functional coating can be selected from any one of 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, or any molar ratio within the range of 1:1 to 3:1. Within the above-mentioned ranges, the concentrations of the primer and functional coatings, as well as the molar ratio of the two coupling agents in the functional coating, are beneficial for constructing an interface layer that combines chemical anchoring and modulus gradient. When the concentration of the primer solution is too low, there are insufficient chemical anchoring points and weak interfacial bonding. When the concentration is too high, the coupling agent molecules self-condense on the fiber surface to form a weak interface layer, which is not conducive to load transfer. When the proportion of aminosilane in the functional coating is too low, the interfacial catalytic effect is weak and the gradient is not obvious. When the proportion is too high, the interfacial region becomes brittle due to excessive cross-linking, which reduces the interfacial toughness.
[0041] Cyanate ester resins exhibit high crosslinking density and good heat resistance after curing, but their matrix toughness is relatively insufficient. Furthermore, the trimerization reaction of the cyanate ester groups requires a specific temperature, and there is competition between the reaction process and the construction of the preferential trimerization gradient in the interfacial region. Therefore, this application selects and controls the cyanate ester resin system. In some embodiments of this application, the cyanate ester resin can be selected from at least one of bisphenol A, bisphenol B, bisphenol F, phenolic, and naphthalene-type cyanate ester resins, or it can be formed by blending cyanate ester resin and bismaleimide resin in a weight ratio of 90:10 to 70:30. The aforementioned cyanate ester resins all possess low dielectric constants, low dielectric losses, and good resistance to damp heat. Among them, bisphenol A and bisphenol F cyanate ester resins have mature processes and moderate costs, while phenolic and naphthalene-type cyanate ester resins exhibit higher crosslinking density and heat resistance. Introducing bismaleimide resin can copolymerize with cyanate ester groups to form an interpenetrating network, improving matrix toughness. When the proportion of bismaleimide resin in the blend is too high, the matrix dielectric loss increases; when the proportion is too low, the toughening effect is not significant. A weight ratio in the range of 90:10 to 70:30 can effectively improve matrix toughness while maintaining low dielectric loss. This application also adds a catalyst to the cyanate ester resin. The catalyst can be selected from at least one of stannous octoate, copper naphthenate, and cobalt acetylacetonate, and the amount of catalyst added is 50-500 ppm. The catalyst can reduce the activation energy of the cyanate group trimerization reaction and promote the curing reaction. If the amount of catalyst added is too low, the curing will be insufficient and the matrix crosslinking density will be insufficient. If the amount added is too high, the curing speed will be too fast, which is not conducive to the construction of the preferential trimerization gradient in the interface region. The amount added is in the range of 50-500 ppm, which can ensure that the curing reaction proceeds normally and reserve a sufficient reaction window for the formation of the interface gradient structure.
[0042] In some embodiments of this application, the TLCP fiber can be a copolymer of p-hydroxybenzoic acid (HBA) and 6-hydroxy-2-naphthoic acid (HNA) thermotropic liquid crystal polymer fiber, wherein the molar ratio of p-hydroxybenzoic acid to 6-hydroxy-2-naphthoic acid can be any molar ratio in the range of 70:30 to 75:25; the monofilament diameter can be selected from any one or any two of 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, and 20μm, i.e., any value in the range of 8-20μm; the multifilament linear density can be selected from any one or any two of 100dtex, 200dtex, 400dtex, 600dtex, 800dtex, 1000dtex, 1500dtex, and 2000dtex, i.e., any value in the range of 100-2000dtex; the fabric can be plain weave or satin weave, and the areal density can be selected from 50g / m². 2 80g / m 2 100g / m 2120g / m 2 150g / m 2 180g / m 2 200g / m 2 The range of values between any one or both of these, i.e., 50-200 g / m³ 2 Any value within the range. The main chain of HBA / HNA copolymer TLCP fiber is composed of rigid aromatic ester segments, which endows the fiber with a low dielectric constant (2.8-3.2@10GHz), low dielectric loss (≤0.003@10GHz), and low density (1.38-1.42g / cm³). 3 It possesses excellent electrical insulation properties; plain weave fabrics offer stable structure and good rigidity, while satin weave fabrics exhibit good drape and curved surface fit, allowing selection based on the rigidity and installation requirements of the solar panel substrate. The melting point of TLCP fibers varies with the molar ratio of HBA to HNA. Correspondingly, the temperature window for solid-state polycondensation treatment is set according to the melting point of the selected TLCP fiber (at least 10°C lower than the melting point). TLCP fibers with different melting points can achieve molecular chain growth and thermal fusion at the warp and weft intersections within the corresponding temperature window.
[0043] Solid-state polycondensation, atmospheric pressure plasma activation, and bilayer silane coupling agent interface treatment work synergistically at the fabric structure scale (thermal fusion at warp and weft intersections to construct a second load transfer channel), the fiber surface chemical scale (introducing polar functional groups to increase anchoring site density), and the interface gradient scale (amino catalysis to construct a transition layer with crosslinking density and modulus gradient). These methods address the insufficient interlaminar and interfacial shear strength of TLCP fiber composites from three levels: macroscopic load transfer, interfacial chemical bonding, and interfacial stress homogenization. None of these interface reinforcement methods introduce components with high dielectric constants or high dielectric losses. While improving interfacial performance, the composite material maintains low dielectric constants and low dielectric losses, achieving a balance between mechanical, interfacial, and dielectric properties. This meets the requirements of satellite flexible solar panel substrates for lightweight structure and high-frequency signal transmission performance.
[0044] Example 1: This example provides a TLCP fiber composite material and its preparation method. The preparation steps are as follows: Solid-state polycondensation in fabric: Plain weave fabric is woven using TLCP fibers with an HBA / HNA molar ratio of 73:27, a monofilament diameter of 12μm, a multifilament linear density of 400dtex, and an initial melting point of 310℃. The fabric surface density is 120g / m². 2 The plain weave fabric was laid flat and fixed in a tube furnace, and a vacuum of ≤100 Pa was applied. The temperature was increased from 250℃ to 295℃ at a rate of 5℃ / h, and held at 295℃ for 6 hours. The fabric was then cooled to room temperature in the furnace. After SSP (Self-Splitting), the fiber strength was 18 cN / dtex, the modulus was 529 cN / dtex, and the elongation at break was 2.8%.
[0045] Atmospheric pressure plasma jet activation: The SSP-treated fabric was continuously treated by a linear atmospheric pressure plasma jet device. The treatment atmosphere was compressed air, the discharge power was 200W, the fabric speed was 3m / min, and the distance between the nozzle and the fabric was 8mm. The front and back sides were treated once each. After treatment, the surface contact angle of the fabric decreased from 78° to 38°, and the surface free energy increased from 36mN / m to 53mN / m.
[0046] KH-560 Primer: Within 15 minutes after plasma treatment, prepare a 1.5wt% KH-560 ethanol / water solution (ethanol:water = 95:5 volume ratio), adjust the pH to 4.5 with acetic acid, immerse the plasma-treated fabric in the solution at room temperature for 5 minutes, remove it and dry it at 70℃ for 20 minutes.
[0047] Functional coating: Prepare a mixed silane coupling agent solution with a molar ratio of KH-560 and KH-550 of 2:1 and a total concentration of 1.5wt%. The solvent is ethanol / water (ethanol:water = 95:5 volume ratio). Adjust the pH to 4.5 with acetic acid. Immerse the base-coated fabric in the solution at room temperature for 10 minutes, and then dry it at 75°C for 30 minutes.
[0048] Prepreg preparation: The solution impregnation method was used to dissolve the BADCy / BMI=80:20 blended resin (catalyst is 200ppm stannous octoate) in methyl ethyl ketone with a solid content of 40wt%. The fabric treated with double silane was immersed in the resin solution, and the resin content was controlled to 42wt% by scraping. The fabric was dried at 100℃ for 10min to obtain the B-stage prepreg.
[0049] Lamination and hot-press curing: [0 / 90] 3s layup, 6 layers, fiber volume fraction of 48%. Heat to 130℃ at 2℃ / min and hold for 1h (pressurized to 0.5MPa), then heat to 190℃ and hold for 3h, and finally heat to 230℃ and hold for 2h. Allow to cool naturally (cooling rate ≤2℃ / min) to room temperature.
[0050] Example 2: This example provides a TLCP fiber composite material and its preparation method. The preparation steps are as follows: Solid-state polycondensation in fabric: A 5-end satin fabric was woven using TLCP fibers with an HBA / HNA molar ratio of 73:27, a monofilament diameter of 12 μm, a multifilament linear density of 400 dtex, and an initial melting point of 310℃. The fabric surface density was 180 g / m². 2 The warp and weft density is 80 threads / 10cm. The satin fabric is laid flat and fixed in a tube furnace, and heated from 255℃ to 300℃ at a rate of 3℃ / h under N2 atmosphere (flow rate 300mL / min). It is held at 300℃ for 4h and then cooled to room temperature in the furnace. After SSP, the fiber strength is 16cN / dtex and the modulus is 700cN / dtex.
[0051] Atmospheric pressure plasma jet activation: The fabric after SSP is continuously treated by a linear atmospheric pressure plasma jet device. The treatment atmosphere is an O2 / N2 mixture (O2:N2=40:60), the discharge power is 250W, the fabric speed is 2m / min, and the distance from the nozzle to the fabric is 10mm.
[0052] KH-560 primer: Prepare a 2.0wt% KH-560 ethanol / water solution (ethanol:water = 93:7 volume ratio), adjust the pH to 4.5 with acetic acid, immerse the plasma-treated fabric in the solution at room temperature for 5 minutes, remove and dry at 75℃ for 25 minutes.
[0053] Functional coating: Prepare a mixed silane coupling agent solution with a molar ratio of KH-560 and KH-550 of 3:1 and a total concentration of 2.0 wt%. Immerse the base-coated fabric in the solution at room temperature for 10 min, and then dry it at 80℃ for 25 min.
[0054] Prepreg preparation: The bisphenol F cyanate resin (BFDCy) was heated to 100°C and melted by hot melt impregnation. 150 ppm of cobalt acetylacetone catalyst was added, and the fabric treated with double silane was impregnated in the resin. The resin content was controlled at 45 wt% to obtain the prepreg.
[0055] Lamination and hot-press curing: [0 / 45 / 90 / -45] 2s layup, 8 layers, fiber volume fraction of 52%. Heat to 140℃ at 2℃ / min and hold for 1.5h (pressurized to 0.7MPa), then heat to 200℃ and hold for 3h, and finally heat to 240℃ and hold for 2h, then cool naturally to room temperature.
[0056] Example 3: This example provides a TLCP fiber composite material and its preparation method. The preparation steps are as follows: Solid-state polycondensation in fabric: Plain weave fabric is woven using TLCP fibers with an HBA / HNA molar ratio of 70:30, a monofilament diameter of 10 μm, a multifilament linear density of 200 dtex, and an initial melting point of 300℃. The fabric surface density is 80 g / m². 2 The plain weave fabric was laid flat and fixed in a tube furnace, and a vacuum of ≤50 Pa was applied. The temperature was increased from 240℃ to 285℃ at a rate of 6℃ / h, and held at 285℃ for 8 hours. The fabric was then cooled to room temperature with the furnace. After SSP (Self-Splitting), the fiber strength was 20 cN / dtex and the modulus was 600 cN / dtex.
[0057] Atmospheric pressure plasma jet activation: The fabric after SSP is continuously treated by a linear atmospheric pressure plasma jet device. The treatment atmosphere is compressed air, the discharge power is 150W, the fabric speed is 5m / min, the distance from the nozzle to the fabric is 6mm, and the front and back sides are treated 3 times each.
[0058] KH-560 primer: Prepare a 0.8wt% KH-560 ethanol / water solution (ethanol:water = 95:5 volume ratio), adjust the pH to 4.0 with acetic acid, immerse the plasma-treated fabric in the solution at room temperature for 5 minutes, remove and dry at 65℃ for 30 minutes.
[0059] Functional coating: Prepare a mixed silane coupling agent solution with a molar ratio of KH-560 and KH-550 of 1:1 and a total concentration of 1.0 wt%. Immerse the base-coated fabric in the solution at room temperature for 10 min, and then dry it at 65°C for 40 min.
[0060] Prepreg preparation: The solution impregnation method was used to dissolve phenolic polycyanate resin (catalyst is 100ppm copper naphthenate) in methyl ethyl ketone with a solid content of 35wt%. The fabric treated with double silane was immersed in the resin solution, and the resin content was controlled by scraping to 38wt%. The prepreg was obtained by drying at 100℃ for 10min.
[0061] Lamination and hot-press curing: [0 / 90] 4s layup, 8 layers, fiber volume fraction of 55%. Heat to 120℃ at 2℃ / min and hold for 2h (pressurized to 0.4MPa), then heat to 180℃ and hold for 3h, and finally heat to 220℃ and hold for 3h, then cool naturally to room temperature.
[0062] Example 4: This example provides a TLCP fiber composite material and its preparation method. The preparation steps are as follows: Solid-state polycondensation in fabric: Plain weave fabric is woven using TLCP fibers with an HBA / HNA molar ratio of 73:27, a monofilament diameter of 12μm, a multifilament linear density of 400dtex, and an initial melting point of 310℃. The fabric surface density is 120g / m². 2 The plain weave fabric is laid flat and fixed in a tube furnace, and the vacuum is drawn to ≤100Pa. The temperature is increased from 250℃ to 295℃ at a heating rate of 5℃ / h, and held at 295℃ for 6 hours. The furnace is then cooled to room temperature.
[0063] Atmospheric pressure plasma jet activation: The fabric after SSP is continuously treated by a linear atmospheric pressure plasma jet device. The treatment atmosphere is compressed air, the discharge power is 350W, the fabric speed is 1m / min, the distance from the nozzle to the fabric is 12mm, and the front and back sides are treated once each.
[0064] KH-560 primer: Prepare a 3.0wt% KH-560 ethanol / water solution (ethanol:water = 90:10 volume ratio), adjust the pH to 5.0 with acetic acid, immerse the plasma-treated fabric in the solution at room temperature for 5 minutes, remove and dry at 80℃ for 15 minutes.
[0065] Functional coating: Prepare a mixed silane coupling agent solution with a molar ratio of KH-560 and KH-550 of 2:1 and a total concentration of 3.0 wt%. Immerse the base-coated fabric in the solution at room temperature for 10 min, and then dry it at 80℃ for 20 min.
[0066] Prepreg preparation: The solution impregnation method was used. The BADCy / BMI=70:30 blended resin was dissolved in methyl ethyl ketone. The fabric treated with double-layer silane was immersed in the resin solution. The resin content was controlled at 42wt% by scraping. The prepreg was obtained by drying at 100℃ for 10min.
[0067] Lamination and hot-press curing: [0 / 90] 3s layup, 6 layers, fiber volume fraction of 48%. Curing conditions: heat treatment at 135℃ for 1.5h, then at 195℃ for 2.5h, then at 235℃ for 2.5h, curing pressure 0.6MPa, and natural cooling to room temperature.
[0068] Comparative Example 1: The difference between this comparative example and Example 1 is that no solid-state polycondensation treatment in the fabric state is performed; instead, commercially available heat-treated TLCP fiber fabric is used directly. Its preparation method includes the following steps: Atmospheric pressure plasma jet activation: Commercially available heat-treated TLCP fiber plain weave fabric (HBA / HNA molar ratio 73:27, monofilament diameter 12μm, multifilament linear density 400dtex, areal density 120g / m²) was used. 2 The tensile strength is 18 cN / dtex and the modulus is 529 cN / dtex. The material is continuously treated by a linear atmospheric pressure plasma jet device. The treatment atmosphere is compressed air, the discharge power is 200W, the fabric speed is 3m / min, the distance from the nozzle to the fabric is 8mm, and the front and back sides are treated once each.
[0069] KH-560 primer: Prepare a 1.5wt% KH-560 ethanol / water solution (ethanol:water = 95:5 volume ratio), adjust the pH to 4.5 with acetic acid, immerse the plasma-treated fabric in the solution at room temperature for 5 minutes, remove and dry at 70℃ for 20 minutes.
[0070] Functional coating: Prepare a mixed silane coupling agent solution with a molar ratio of KH-560 and KH-550 of 2:1 and a total concentration of 1.5wt%. Immerse the base-coated fabric in the solution at room temperature for 10 minutes, and then dry it at 75°C for 30 minutes.
[0071] Prepreg preparation: The solution impregnation method was used to dissolve the BADCy / BMI=80:20 blended resin (catalyst is 200ppm stannous octoate) in methyl ethyl ketone, with a solid content of 40wt%. The fabric was immersed in the resin solution, and the resin content was controlled to 42wt% by scraping. The fabric was dried at 100℃ for 10min to obtain the B-stage prepreg.
[0072] Lamination and hot-press curing: [0 / 90] 3s layup, 6 layers, fiber volume fraction of 48%. Heat to 130℃ at 2℃ / min and hold for 1h (pressurized to 0.5MPa), then heat to 190℃ and hold for 3h, and finally heat to 230℃ and hold for 2h, then cool naturally to room temperature.
[0073] Comparative Example 2: The difference between this comparative example and Example 1 is that: no atmospheric pressure plasma activation treatment is performed; the fabric is directly coated with a coupling agent after solid-state polycondensation treatment. Its preparation method includes the following steps: Solid-state polycondensation in fabric: Plain weave fabric is woven using TLCP fibers with an HBA / HNA molar ratio of 73:27, a monofilament diameter of 12μm, a multifilament linear density of 400dtex, and an initial melting point of 310℃. The fabric surface density is 120g / m². 2 The plain weave fabric is laid flat and fixed in a tube furnace, and the vacuum is drawn to ≤100Pa. The temperature is increased from 250℃ to 295℃ at a heating rate of 5℃ / h, and held at 295℃ for 6 hours. The furnace is then cooled to room temperature.
[0074] KH-560 primer: Prepare a 1.5wt% KH-560 ethanol / water solution (ethanol:water = 95:5 volume ratio), adjust the pH to 4.5 with acetic acid, immerse the SSP-treated fabric in the solution at room temperature for 5 minutes, remove and dry at 70℃ for 20 minutes.
[0075] Functional coating: Prepare a mixed silane coupling agent solution with a molar ratio of KH-560 and KH-550 of 2:1 and a total concentration of 1.5wt%. Immerse the base-coated fabric in the solution at room temperature for 10 minutes, and then dry it at 75°C for 30 minutes.
[0076] Prepreg preparation: The solution impregnation method was used to dissolve the BADCy / BMI=80:20 blended resin (catalyst is 200ppm stannous octoate) in methyl ethyl ketone, with a solid content of 40wt%. The fabric was immersed in the resin solution, and the resin content was controlled to 42wt% by scraping. The fabric was dried at 100℃ for 10min to obtain the B-stage prepreg.
[0077] Lamination and hot-press curing: [0 / 90] 3s layup, 6 layers, fiber volume fraction of 48%. Heat to 130℃ at 2℃ / min and hold for 1h (pressurized to 0.5MPa), then heat to 190℃ and hold for 3h, and finally heat to 230℃ and hold for 2h, then cool naturally to room temperature.
[0078] Comparative Example 3: This comparative example differs from Example 1 in that it only uses KH-560 single-layer coupling agent treatment, without setting a functional coating containing KH-550, and the concentration of the KH-560 primer solution is increased to 1.5 wt%. Its preparation method includes the following steps: Solid-state polycondensation in fabric: Plain weave fabric is woven using TLCP fibers with an HBA / HNA molar ratio of 73:27, a monofilament diameter of 12μm, a multifilament linear density of 400dtex, and an initial melting point of 310℃. The fabric surface density is 120g / m². 2 The plain weave fabric is laid flat and fixed in a tube furnace, and the vacuum is drawn to ≤100Pa. The temperature is increased from 250℃ to 295℃ at a heating rate of 5℃ / h, and held at 295℃ for 6 hours. The furnace is then cooled to room temperature.
[0079] Atmospheric pressure plasma jet activation: The fabric after SSP is continuously treated by a linear atmospheric pressure plasma jet device. The treatment atmosphere is compressed air, the discharge power is 200W, the fabric speed is 3m / min, the distance from the nozzle to the fabric is 8mm, and the front and back sides are treated once each.
[0080] KH-560 primer: Prepare a 1.5wt% KH-560 ethanol / water solution (ethanol:water = 95:5 volume ratio), adjust the pH to 4.5 with acetic acid, immerse the plasma-treated fabric in the solution at room temperature for 5 minutes, remove and dry at 70℃ for 20 minutes.
[0081] Prepreg preparation: The solution impregnation method was used to dissolve the BADCy / BMI=80:20 blended resin (catalyst is 200ppm stannous octoate) in methyl ethyl ketone, with a solid content of 40wt%. The fabric was immersed in the resin solution, and the resin content was controlled to 42wt% by scraping. The fabric was dried at 100℃ for 10min to obtain the B-stage prepreg.
[0082] Lamination and hot-press curing: [0 / 90] 3s layup, 6 layers, fiber volume fraction of 48%. Heat to 130℃ at 2℃ / min and hold for 1h (pressurized to 0.5MPa), then heat to 190℃ and hold for 3h, and finally heat to 230℃ and hold for 2h, then cool naturally to room temperature.
[0083] Comparative Example 4: This comparative example differs from Example 1 in that it does not undergo atmospheric pressure plasma activation treatment or any silane coupling agent treatment; the fabric is directly impregnated with resin after solid-state polycondensation treatment. Its preparation method includes the following steps: Solid-state polycondensation in fabric: Plain weave fabric is woven using TLCP fibers with an HBA / HNA molar ratio of 73:27, a monofilament diameter of 12μm, a multifilament linear density of 400dtex, and an initial melting point of 310℃. The fabric surface density is 120g / m². 2 The plain weave fabric is laid flat and fixed in a tube furnace, and the vacuum is drawn to ≤100Pa. The temperature is increased from 250℃ to 295℃ at a rate of 5℃ / h (takes 9h), held at 295℃ for 6h, and then cooled to room temperature with the furnace.
[0084] Prepreg preparation: The solution impregnation method was used to dissolve the BADCy / BMI=80:20 blended resin (catalyst is 200ppm stannous octoate) in methyl ethyl ketone with a solid content of 40wt%. The SSP fabric was then immersed in the resin solution, and the resin content was controlled to 42wt% by scraping. The fabric was then dried at 100℃ for 10min to obtain the B-stage prepreg.
[0085] Lamination and hot-press curing: [0 / 90] 3s layup, 6 layers, fiber volume fraction of 48%. Heat to 130℃ at 2℃ / min and hold for 1h (pressurized to 0.5MPa), then heat to 190℃ and hold for 3h, and finally heat to 230℃ and hold for 2h, then cool naturally to room temperature.
[0086] Comparative Example 5: This comparative example uses T800 carbon fiber / epoxy resin composite material, a conventional satellite solar panel substrate material system. Its preparation method includes the following steps: T800 carbon fiber fabric and epoxy resin were used to prepare a prepreg using conventional prepreg process. The prepreg was laid up in 3s, 6 layers were formed, and then hot-pressed and cured to obtain a carbon fiber / epoxy resin composite substrate. A 0.05mm polyimide insulating film was additionally attached to the surface of the substrate.
[0087] The materials prepared in the above embodiments and comparative examples were tested. The dielectric constant (Dk) and dielectric loss tangent (Df) were tested using the dielectric resonator method (open cavity method, referring to GB / T 7265.2-1987) at a frequency of 10 GHz. Tensile strength and tensile modulus were determined according to GB / T 1447-2005 (Test Method for Tensile Properties of Fiber Reinforced Plastics). Flexural strength was determined according to GB / T 1449-2005 (Test Method for Flexural Properties of Fiber Reinforced Plastics). Interlaminar shear strength (ILSS) was determined using the short beam method according to GB / T 1450.1-2005 (Test Method for Interlaminar Shear Strength of Fiber Reinforced Plastics). Interfacial shear strength (IFSS) was determined using the single-fiber micro-debonding method (calculated by dividing the debonding force between the fiber and resin droplets by the embedding area). Water absorption was determined according to GB / T 1462-2005 (Test Method for Water Absorption of Fiber Reinforced Plastics). Density was determined according to GB / T The density and relative density of fiber-reinforced plastics shall be determined in accordance with GB / T 2572-2005 (Test Method for Average Linear Expansion Coefficient of Fiber-Reinforced Plastics).
[0088] Table 1. Dielectric property test results of the examples and comparative examples.
[0089] Table 2. Mechanical and physical performance test results of the examples and comparative examples.
[0090] As shown in Tables 1 and 2, the TLCP fiber composites prepared in Examples 1-4 all exhibit low dielectric constants (2.76-2.88), low dielectric losses (0.0028-0.0042), high strength (tensile strength 380-480 MPa, flexural strength 480-560 MPa), and excellent interlayer / interfacial properties (ILSS 48-55 MPa, IFSS 42-48 MPa), demonstrating balanced overall performance, and none of them require an additional insulating layer. This is attributed to the synergistic interface treatment employed in each example: firstly, solid-state polycondensation in the fabric state allows the fiber molecular chains to continue growing in the solid phase, and the fibers at the warp and weft intersections are thermally fused to form a second load transfer channel; then, atmospheric pressure plasma activation introduces oxygen-containing polar functional groups, increasing the density of coupling agent anchoring sites; subsequently, a bilayer silane coupling agent is used to construct the interface layer, causing the cyanate ester groups in the interface region to preferentially trimerize and form a gradient transition layer of crosslinking density and modulus, eliminating interfacial stress concentration. Stepped hot pressing curing ensures the stable formation of the interface gradient structure and the curing of the resin matrix.
[0091] Comparative Example 1, without solid-state polycondensation treatment, had ILSS and IFSS of 44 MPa and 38 MPa, respectively. In contrast, Example 1, after solid-state polycondensation treatment, achieved ILSS of 52 MPa and IFSS of 46 MPa, representing increases of approximately 18% and 21%, respectively. Given that Comparative Example 1 used pre-treated commercial fibers and that the fiber's mechanical properties were comparable to those of Example 1 after solid-state polycondensation, the increase in ILSS was primarily attributed to the thermal fusion effect at the warp and weft intersections during solid-state polycondensation. This physical fusion point constitutes a second load transfer channel distinct from the fiber-matrix interface, reducing reliance on a single interface.
[0092] Comparative Example 2 omitted the atmospheric pressure plasma activation step, and its IFSS was only 34 MPa, 26% lower than that of Example 1 (46 MPa), while the ILSS decreased from 52 MPa to 42 MPa. The reason is that without plasma treatment, the density of oxygen-containing polar functional groups (hydroxyl groups) on the fiber surface is low, and there are insufficient sites for condensation anchoring of silanols generated by the hydrolysis of silane coupling agent. The chemical bonding density between the coupling agent layer and the fiber surface decreases significantly, and the interfacial load transfer efficiency decreases accordingly.
[0093] Comparative Example 3, which only used a single layer of KH-560 without the addition of a functional coating containing KH-550, had an IFSS of 36 MPa and an ILSS of 44 MPa, representing reductions of 22% and 15% respectively compared to Example 1. The absence of the amino-containing KH-550 functional coating resulted in a lack of amino catalytic sites in the interfacial region. This led to the disappearance of the preferential trimerization effect of cyanate ester groups on the fiber surface, causing the crosslinking density in the interfacial region to become uniform with that of the bulk matrix. Consequently, a gradient transition layer between crosslinking density and modulus could not be formed, resulting in interfacial stress concentration and performance degradation.
[0094] Comparative Example 4, without any surface treatment, had an ILSS of only 30 MPa and an IFSS of only 22 MPa. Example 1, after a full set of interface treatments, reached 52 MPa and 46 MPa, respectively, with increases of approximately 73% and 109%. This indicates that the synergistic effect of solid-state polycondensation cross-point fusion, atmospheric pressure plasma activation, and double-layer silane coupling agent treatment can significantly improve interlayer and interface properties.
[0095] Comparative Example 5 uses T800 carbon fiber / epoxy resin composite material, a commonly used material system for satellite solar panel substrates. Its tensile strength (1100 MPa) and flexural strength (1000 MPa) are higher than those of TLCP fiber composite material, but its dielectric properties are significantly different: Dk=4.30, Df=0.018, and the dielectric loss is about 4 times higher than that of Example 1 (Df=0.0042), making it unsuitable for scenarios with strict requirements for high-frequency signal transmission quality. Furthermore, the density of the carbon fiber / epoxy system is 1.56 g / cm³. 3 Furthermore, an additional polyimide insulating film needs to be applied (increasing the process and weight); the TLCP fiber composite material of this application has a density of only 1.32 g / cm³. 3 TLCP fibers are electrically insulating and do not require an insulation layer, giving them advantages in terms of lightweighting and simplified manufacturing processes.
[0096] Example 2 uses satin weave fabric and quasi-isotropic layup, with tensile and bending properties slightly better than those of Example 1 using plain weave fabric, making it suitable for flexible solar panel surface bonding scenarios; Example 3 increases the KH-550 ratio to 1:1, with Df as low as 0.0028, indicating that increasing the density of amino catalytic sites helps to improve the degree of cyanate trimerization in the interfacial region, further reducing dielectric loss; Example 4 increases the coupling agent concentration to 3.0 wt%, with mechanical properties comparable to Example 1.
[0097] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0098] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a TLCP fiber composite material, characterized in that, Includes the following steps: The TLCP fiber fabric is subjected to solid-state polycondensation treatment at a temperature below the melting point of the TLCP fiber to obtain the first fabric. The first fabric is subjected to atmospheric pressure plasma activation treatment to obtain the second fabric; An epoxy silane coupling agent base coat and a functional coating are sequentially coated on the fiber surface of the second fabric to form a double-layer silane coupling agent interface layer. The functional coating contains an epoxy silane coupling agent and an amino silane coupling agent to obtain the third fabric. The third fabric is impregnated with cyanate ester resin, and then cured by lay-up and stepped hot pressing to obtain TLCP fiber composite material.
2. The preparation method according to claim 1, characterized in that, The solid-state polycondensation treatment is carried out at a temperature of 250-300℃, which is more than 10℃ lower than the melting point of the TLCP fiber; the holding time of the solid-state polycondensation treatment is 2-12h, and the heating rate is 2-10℃ / h; the solid-state polycondensation treatment is carried out under vacuum or inert atmosphere.
3. The preparation method according to claim 2, characterized in that, The solid-state polycondensation treatment is carried out at a temperature of 280-300℃, with a holding time of 4-8 hours and a heating rate of 3-6℃ / h.
4. The preparation method according to claim 1, characterized in that, The atmospheric pressure plasma activation treatment uses an atmospheric pressure plasma jet with a discharge power of 100-500W, a fabric speed of 1-10m / min, a nozzle-to-fabric distance of 3-15mm, and a treatment atmosphere of compressed air or O2 / N2 mixture.
5. The preparation method according to claim 1, characterized in that, The epoxy silane coupling agent is γ-glycidyl etheroxypropyltrimethoxysilane, and the amino silane coupling agent is γ-aminopropyltriethoxysilane; both the base coating and the functional coating are dried after application, with the drying temperature being 60-80℃ and the drying time being 10-40 min.
6. The preparation method according to claim 1, characterized in that, The cyanate ester resin is a bisphenol A, bisphenol B, bisphenol F, phenolic, or naphthalene cyanate ester resin, or a resin formed by blending cyanate ester resin and bismaleimide resin in a weight ratio of 90:10 to 70:30; the cyanate ester resin further includes a catalyst, which is selected from at least one of stannous octoate, copper naphthenate, and cobalt acetylacetonate, and the amount of catalyst added is 50-500 ppm.
7. The preparation method according to claim 1, characterized in that, The TLCP fiber is a thermotropic liquid crystal polymer fiber copolymerized with p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, wherein the molar ratio of p-hydroxybenzoic acid to 6-hydroxy-2-naphthoic acid is (70-75):(25-30); the monofilament diameter of the TLCP fiber is 8-20 μm, and the multifilament linear density is 100-2000 dtex; the TLCP fiber fabric is a plain weave or satin weave fabric with an areal density of 50-200 g / m². 2 .
8. The preparation method according to claim 1, characterized in that, The stepped hot-press curing process includes: holding at 120-140℃ for 1-2 hours, then holding at 180-200℃ for 2-3 hours, and then holding at 220-240℃ for 2-3 hours, with a curing pressure of 0.4-0.7 MPa.
9. A TLCP fiber composite material obtained by the preparation method according to any one of claims 1 to 8.
10. The application of the TLCP fiber composite material according to claim 9 in a satellite flexible solar panel substrate.